Comprehensive review on ethnobotanical uses, phytochemistry, biological potential and toxicology of Parthenium hysterophorus L.: A journey from noxious weed to a therapeutic medicinal plant. (5th December 2021) - Kaur, Loveleen; Malhi, Dharambeer Singh; Cooper, Raymond; Kaur, Manvinder; Sohal, Harvinder Singh; Mutreja, Vishal; Sharma, Ajay
Abstract: Ethno-pharmacological relevance: Parthenium hysterophorus L. is a noxious weed and a species of flowering plant in the Asteraceae family. It is regarded as the seventh most deadly weed in the world: harmful to both humans and livestock. It is widely known as Congress Grass or Feverfew. Despite its pitfalls, P. hysterophorus bestows medicinal effects. Although prolific in nature and difficult to control, many novel applications of this controversial herb have been discovered as an approach to manage the weed. Aim: The current review aims to compile all the ethnobotanical, phytochemistry, biological activities and utilities, clinical studies and toxicity data available on P. hysterophorus and its major chemical constituent parthenin. Materials and methods: Extensive literature surveyed Google search, Google scholar, Wiley online library, Elsevier, Springer, Science direct, American Chemical Society, Royal Society of Chemistry and Research Gate. Result: According to the study, P. hysterophorus is utilized as a traditional medicine throughout Central America and the Caribbean. It can be used to treat skin infections, dermatitis, amoebic dysentery, and as an analgesic in the treatment of muscular rheumatism. The extracts obtained from P. hysterophorus have anti-inflammatory, antioxidant, larvicidal, anti-microbial, insecticidal, hypoglycaemic and anti-cancer activity. Conclusion: The earlier investigations confirmed that P. hysterophorus has numerous traditional and biological applications. However, the scientific data are limited in clinical and toxicological studies. Therefore, further research is required on clinical and toxicological aspects to understand the complete potential and effects of P. hysterophorus . Graphical abstract: Image 1 Highlights: P. hysterophorus originally is an invasive plant originated in Americas and presently invades about forty countries. Traditionally, it is used for the cure of a variety of ailments like fevers, diarrhoea, herpes, malaria, diabetes, heart troubles, etc. P. hysterophorus is also known to possess variety of pharmacological properties viz. analgesic, anticancer, antioxidant, antimicrobial etc. P. hysterophorus is a rich source of various bioactive phytoconstituents like alkaloids, flavonoids, phenols and terpenoids. Sesquiterpene lactones are the major bioactive phytoconstituents present in P. hysterophorus .